Environmental requirements for the hatchery rearing of African catfish Clarias Gariepinus (Pisces: Clariidae) larvae and juveniles - Britz, Peter Jacobus (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1988)
Inadequate seed production has historically been a factor limiting the commercial culture of Clarias gariepinus. The need to determine the environmental requirements of larvae was identified, in order to facilitate their successful mass rearing in hatcheries. The effects of key environmental factors on the growth, survival and aspects of the behaviour of C. gariepinus larvae and juveniles were investigated under controlled conditions. A strong emphasis was placed on the interpretation of the observed responses in terms of the natural history of the animal. Larvae were obtained by artificially inducing and spawning feral adult broodfish. Larval growth rates were highest in the temperature range 26-33ºC, with a peak at 30ºC. Survival of larvae was high between 22 and 33ºC. The final temperature preferendum of juveniles, determined in a thermal gradient was 30ºC, and it was concluded that this temperature is probably optimal for most of the physiological processes of the animal. Larvae and juveniles displayed strong negative phototaxis. When reared under different photoperiod regimes, larval growth increased with longer dark periods, however a similar rate of mortality was recorded in all photoperiod treatments. The provision of cover was found to enhance larval growth under conditions of continual light (24L/OD), however under conditions of continual darkness (OL/24D) similar growth rates were recorded regardless of the presence or absence of cover. All growth rates in continual darkness (OL/24D) were higher than those in continual light (24L/OD), regardless of whether cover was provided or not. It was concluded that a OL/24D photoperiod is optimal for larval rearing. At salinities between 0 and 5% similar growth and mortality rates of larvae were recorded. At 7.5 % larval growth and survival rates were lower, and at 10 % all larvae died within 48 hours. The 96h-LCSO for unionised ammonia was found to be 2.3 mg/l. The cytological effects of unionised ammonia were evident as degenerative changes in the gill and liver tissues. In an investigation of tank hygiene, it was found that larval growth and survival rates were highest in tanks not cleaned at all. As the frequency of tank cleaning increased, the growth and survival rates of larvae decreased. When reared at densities ranging from 45-450/1, larval growth was found to be density dependent. A model of hatchery productivity (number larvae of standard size produced/time/vol.) was developed based on the density dependent nature of larval growth. The model predicts that maximum productivity, will be achieved at a rearing density of 1400/1. The high growth and survival rates obtained over a broad range of each environmental parameter investigated serve to explain how larvae survive and grow in their unstable floodplain habitat in nature. The broad environmental tolerances of C. gariepinus are of benefit with respect to the culture of larvae, as successful larval rearing is possible over a fairly wide range of environmental conditions.
Keywords: Catfishes -- Africa; Fish culture; Clariidae; Clarias